URBAN HEAT ISLAND PADA KOTA INDUSTRI - Andhyka Putra Arie Gayo (STKIP PGRI Situbondo, 2023)
The industrial revolution provides opportunities in changing people's lives from agrarian economic activities to industrial-based economies so that many people massively carried out the phenomenon of migration. The impact of industry causes a vulnerable area in climate change which is currently increasingly large in intensity. This research used a qualitative research method with a descriptive approach. The type of data used in this study was obtained from secondary data, namely literature studies in the form of books, articles and other sources of information. Industrial areas are potential locations of UHI effects despite having a relatively lower population. Its change land cover affect surface temperature increases and humidity decreases. Building materials absorb solar heat, and release it at night so that the environment in the industrial area felt warm. For the industrial area, it is better to be given green vegetation around the region to reduce the occurrence of UHI so that it creates a comfortable life.